2011
DOI: 10.1007/s10646-011-0723-0
|View full text |Cite
|
Sign up to set email alerts
|

Acute effects of pure cylindrospermopsin on the activity and transcription of antioxidant enzymes in tilapia (Oreochromis niloticus) exposed by gavage

Abstract: The cyanobacterial toxin cylindrospermopsin (CYN) is a widely distributed contaminant of freshwater systems with the consequent risk for human and wildlife, particularly fish. However, CYN toxicity data on fish are still scarce. It is known that CYN inhibits glutathione synthesis and this could contribute to oxidative damage. In the present work tilapia (Oreochromis niloticus) were exposed by gavage to 200 and 400 μg/kg bw of pure CYN and sacrificed after 24 h. The activity and relative mRNA expression by real… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
46
1
1

Year Published

2012
2012
2017
2017

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 52 publications
(51 citation statements)
references
References 58 publications
3
46
1
1
Order By: Relevance
“…Moreover, vitamin E per se did not induce any significant changes in this enzymatic activity in the present work, while pretreatment with 45 mg NAC/fish/day induced GPx activity (Guti errez-Praena et al, 2012d). In this study, the kidney was not affected by CYN exposure, in accordance with previous studies (Guti errez-Praena et al, 2012d;Puerto et al, 2011b).…”
Section: Fig 2 Superoxide Dismutase (Sod) (A) and Catalase (Cat) (Bsupporting
confidence: 92%
See 2 more Smart Citations
“…Moreover, vitamin E per se did not induce any significant changes in this enzymatic activity in the present work, while pretreatment with 45 mg NAC/fish/day induced GPx activity (Guti errez-Praena et al, 2012d). In this study, the kidney was not affected by CYN exposure, in accordance with previous studies (Guti errez-Praena et al, 2012d;Puerto et al, 2011b).…”
Section: Fig 2 Superoxide Dismutase (Sod) (A) and Catalase (Cat) (Bsupporting
confidence: 92%
“…Glutathione peroxidase (GPx; EC 1.11.1.9) activity was assayed by following the rate of NADPH oxidation at 340 nm by the coupled reaction with glutathione reductase (Puerto et al, 2011b). The specific activity was determined using the extinction coefficient of 6.22 mM À1 cm À1 .…”
Section: Antioxidant Enzymesmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been suggested that CYP450 metabolites may be responsible for the toxicity observed, although CYN metabolites have not been identified so far [15]. Oxidative stress is also involved in CYN toxicity, as it increases intracellular ROS production, reduces GSH [127], and induced changes in the activity of various oxidative stress biomarkers in vivo and in vitro [4,128,129]. Liver and kidney have been described as the main target organs of this toxin in vivo.…”
Section: Cylindrospermopsinmentioning
confidence: 99%
“…Em estudo utilizando a toxina Cilindrospermopsina em peixe foi evidenciado que a expressão gênica e a atividade das enzimas Glutationa Peroxidase e Glutationa-S-transferase são afetadas contribuindo para danos oxidativos (PUERTO et al, 2011).…”
Section: Bbr -Biochemistry and Biotechnology Reportsunclassified